Effects of saccadic eye movements on postural control in older adults - Aguiar, Stefane Aline; Polastri, Paula Fávaro [UNESP]; Godoi, Daniela; Moraes, Renato; Barela, José Angelo [UNESP]; Rodrigues, Sérgio Tosi [UNESP] (American Psychological Association (APA), 2015)
Saccadic eye movements have been shown to affect posture by decreasing the magnitude of body sway in young adults. However, there is no evidence of how the search for visual information that occurs during eye movements affects postural control in older adults. The purpose of the present study was to determine the influence of saccadic eye movements on postural control in older adults while they stood on 2 different bases of support. Twelve older adults stood upright in 70-s trials under 2 stance conditions (wide and narrow) and 3 gaze conditions (fixation, saccadic eye movements at 0.5 Hz, and saccadic eye movements at 1.1 Hz). Head and trunk sway amplitude and mean sway frequency were measured in both the anterior/posterior (AP) and medial/lateral (ML) directions. The results showed that the amplitude of body sway was reduced during saccades compared with fixation, as previously observed in young adults. However, older adults exhibited similar sway amplitude and frequency in the AP direction under the wide and narrow stance conditions, which is different from observations in young adults, who display larger sway in a narrow stance compared with a wide stance while performing saccades. These results suggest that although older adults are affected by saccadic eye movements by a decrease in the amplitude of body sway, as observed in young adults, they present a more rigid postural control strategy that does not allow larger sway during a more challenging stance condition.
Keywords: Aging; Eye movements; Posture; Saccades; Visual information